Malignant Gastrointestinal Neuroectodermal Tumor in the Right Heart: A Report of an Extremely Rare Case Presenting With a Cardiac Mass - Li, Zhiwen; Pu, Xiaohong; He, Lu; Fu, Yao; Li, Lin; Xu, Yuemei; Guan, Wenyan; Fan, Xiangshan (Frontiers in Cardiovascular Medicine, 2021)
Malignant gastrointestinal neuroectodermal tumor (GNET) is an extremely rare soft tissue sarcoma and has been designated as a new entity recently. At present, GNET virtually exclusively occurs in the gastrointestinal tract. Here we report a case of extra-GNET that arose in the right heart. A 62-year-old male complained of chest distress and breathing difficulty while lying down at night for over 1 month at admission. The radiological findings revealed an occupying lesion involving the right atrium and the right ventricle without any abdominal abnormalities. The patient then underwent a surgical resection. Microscopically, neoplastic cells proliferated in the pattern of nests and sheets with fibrous separation. Focal areas with cellular dyscohesion imparted a vague pseudopapillary pattern. These tumor cells were small to medium in size with fine chromatin and predominantly pale eosinophilic cytoplasm. The nuclei were typically round to oval with somewhat irregular contours and contained small nucleoli. The mitotic figures were easily found. Immunohistochemically, the neoplastic cells were positive for S100 and SOX-10 but negative for HMB-45, A103, and CD99. EWSR1–AFTF1 rearrangement was detected by fluorescence in situ hybridization and further confirmed by whole-transcriptome sequence analysis. The patient had pulmonary metastasis 8 months later and soon died of the disease. The overall survival of the patient was 20 months. In summary, we reported an extremely rare case of cardiac GNET, indicating that the location of GNET should not be confined to the GI tract as initially defined. Due to the lack of a specific effective treatment and the occurrence of early metastasis, cardiac GNET conferred a poor prognosis. More clinical and experimental studies are warranted to better manage this disease in the future.